Kulturnoumetniško delovanje Slovencev v slovanskih deželah do začetka prve svetovne vojne - Gantar Godina, Irena (Dve domovini, 2001)
The contribution is a short survey on Slovene artists, cultural workers and learned people that went to Slavic countries until the year 1918, with the stress on many specificity, which distinguishes such "emigration" from the "real" emigration.
Keywords: ...-1914; Central Europe; Eastern Europe; kulturno življenje; Slovenci; Slovenes; slovenska kultura; slovenski izseljenci; Srednja Evropa; Vzhodna Evropa